Effects of long working hours on metabolic dysfunction-associated steatotic liver disease, with and without increased alcohol intake, in healthy workers: A 10-year cohort study - Yesung Lee; Woncheol Lee (PLoS ONE, 2025)
Long working hours are increasingly recognized as a significant occupational hazard linked to various adverse health outcomes. This study aimed to assess how prolonged working hours relate to the subsequent development of metabolic dysfunction-associated steatotic liver disease (MASLD) and metabolic and alcohol-associated liver disease (MetALD), based on a newly proposed classification system. We analyzed data from 117,354 Korean employees who underwent at least two abdominal ultrasound examinations between 2012 and 2023. Long working hours referred to a weekly workload of at least 60 hours. The primary outcome was the incidence of steatotic liver disease, categorized as MASLD or MetALD. A total of 28,361 new cases were identified over 627,094 person-years of follow-up. Cox proportional hazards models were used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). Participants working ≥60 hours per week had a higher risk of developing MASLD (adjusted HR 1.17, 95% CI 1.03–1.32) and MASLD+MetALD (adjusted HR 1.18, 95% CI 1.05–1.33) compared with those working 35–59 hours per week. Subgroup analyses indicated that the association was especially pronounced among individuals aged ≤47 years and in men. These results suggest that prolonged working hours contribute to an increased risk of MASLD and MASLD+MetALD, particularly in younger and male populations, emphasizing the importance of occupational health interventions.